1977
DOI: 10.3133/pp655m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phreatophyte removal on water quality in the Gila River Phreatophyte Project area, Graham County, Arizona

Abstract: The following factors may be used to convert the English units to the International System units (SI). This report contains both the English and SI units equivalents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Results reported by Laney (1977) and by McQueen and Miller (1972) showed that water in the unsaturated zone may have relatively high solute concentrations compared with the underlying ground water. In studies of movement of nitrate through the unsaturated zone in southern and central California, Pratt and Adrian0 (1973) and Pratt and others (1972) measured the moisture content of soil cores taken at various depths and determined nitrate by extracting the solutes with water.…”
Section: Water Chemistry and Movement In The Unsaturated Zonementioning
confidence: 93%
See 2 more Smart Citations
“…Results reported by Laney (1977) and by McQueen and Miller (1972) showed that water in the unsaturated zone may have relatively high solute concentrations compared with the underlying ground water. In studies of movement of nitrate through the unsaturated zone in southern and central California, Pratt and Adrian0 (1973) and Pratt and others (1972) measured the moisture content of soil cores taken at various depths and determined nitrate by extracting the solutes with water.…”
Section: Water Chemistry and Movement In The Unsaturated Zonementioning
confidence: 93%
“…A vacuum is then applied, and water that collects is later withdrawn by applying compressed gas (Wood, 1976). Samples of soil moisture and water in the unsaturated zone in bottom land adjacent to the Gila River in the upper part of the San Carlos reservoir area, Arizona, were obtained by a somewhat similar procedure (Laney, 1977). Methods of obtaining soil extracts are in common use in soil chemistry work (U.S. Salinity Laboratory Staff, 1954), and such procedures were used in the San Carlos reservoir area by McQueen and Miller (1972).…”
Section: Water Chemistry and Movement In The Unsaturated Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Although ground water quality changes are known to be associated with atmospheric moisture anomalies, only a few attempts have been made to establish the degree of association and the temporal (lag time between moisture anomalies and quality changes) and geographical relationships involved (Krothe and Libra, 1983;Whittemore, 1978;Laney, 1977). In order to do so, several long term Kansas water quality records were correlated with precipitation and selected derived climatic indices.…”
Section: Climatic Indices and Proceduresmentioning
confidence: 99%